Legal Philosophy about the Performance of the Indonesian National Police - Erlyn Indarti (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study is intended to absorb various aspirations and information about all aspects of police performances.It is also projected so that the ranks of the police can guarantee openness and accessibility to comprehensiveinformation about their performance. Through this study, the impact of the implementation of the policeprograms and activities which are then realized through their performances can thus be examined carefully.With this in mind, police legitimacy and community support are expected to flourish. It can be said, the studyis actually a kind of ‘tool’ that is important in the effort of raising partnerships as well as synergistic jointproblem solving among the police, stakeholders, and the public. Through this study, meaningful dialoguein order to hear, understand, accept, solve problems, and then meet the needs of the police, can take place.